2001
DOI: 10.1111/j.1572-0241.2001.05269.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron accumulation in the liver of male patients with Wilson's disease

Abstract: Iron overload related to hypoceruloplasminemia may be clinically important, particularly in male patients with Wilson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…The compound overload of copper and iron in the patients was reported in detail elsewhere. [15][16][17] Histochemical tests for cuprothioneins should be positive in this disease, but were negative in one patient because of a sampling error. Because ceruloplasmin is a major ferroxidase, hypoceruloplasminemic patients are also affected by iron overload.…”
Section: Patients With Hemochromatosis Wilson Disease and Dubin-johnmentioning
confidence: 90%
See 1 more Smart Citation
“…The compound overload of copper and iron in the patients was reported in detail elsewhere. [15][16][17] Histochemical tests for cuprothioneins should be positive in this disease, but were negative in one patient because of a sampling error. Because ceruloplasmin is a major ferroxidase, hypoceruloplasminemic patients are also affected by iron overload.…”
Section: Patients With Hemochromatosis Wilson Disease and Dubin-johnmentioning
confidence: 90%
“…Their hepatocellular lysosomes might thus be shared by cuprothioneins and iron complex. [15][16][17] The histochemistry for iron and copper is not so sensitive that X-ray microanalysis is recommended for the liver specimens obtained from patients with Wilson disease (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral Cp is also depleted in Wilson’s disease, which is primarily a disorder of copper homeostasis, caused by a genetic mutation to ATP7b (Bull et al, 1993). Copper accumulates in liver and brain, along with iron (Shiono et al, 2001; Litwin et al, 2013). Why does iron also accumulate as a result of the disease?…”
Section: Iron Accumulation In the Brainmentioning
confidence: 99%
“…Aceruloplasminemia first found in a Japanese patient is a severe type of iron overload syndrome, 14 and subsequent studies confirmed that hypoceruloplasminemic male patients with Wilson disease were also affected by hepatic iron overload. 6 Subcellular iron first stimulates synthesis of apoferritin containing phosphorus atoms in its core. Thus, ferritin grains polymerized in lysosomes, namely hemosiderin, simultaneously yield specific X-rays of iron and phosphorus.…”
Section: Mpaired Secretion Of Copper Into Bile Is Causedmentioning
confidence: 99%
“…For example, copper overload might be associated with iron overload in hypoceruloplasminemic patients, or replaced by iron overload after long-term chelation therapy due to further reduced levels of ceruloplasminemia. 6 Without special stain or microanalysis of biopsy liver specimens, misdiagnosis or late diagnosis may occur in some patients. When liver specimens were processed with a standard fixative solution of a 2.0% osmium tetroxide, most cupprothioneins were lost during the subsequent processes of embedding, sectioning, and staining for X-ray probe microanalysis.…”
Section: Introductionmentioning
confidence: 99%